2007
DOI: 10.1007/s11103-007-9148-9
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and molecular characterisation of a Δ8-sphingolipid-desaturase from Nicotiana tabacum closely related to Δ6-acyl-desaturases

Abstract: Investigation on the absence of Delta(6)-desaturase activity in Nicotiana tabacum has led to the cloning of a new desaturase gene from this organism (NTDXDES) that exhibited unexpected biochemical activity. Cladistic analysis shows clustering of NTDXDES together with functional Delta(6)-acyl-desaturases of near Solanales plants, such as Borago and Echium. This group lies apart from that of previously characterised Delta(8)-sphingolipid-desaturases, which also includes two putative tobacco members identified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
1
17
1
Order By: Relevance
“…Although slight, but significant, dissimilarities in the LCB profiles of plant leaves exist between our data and those of others [17,21,33], they are unlikely due to technical issues but rather reflect differences in the physiological status of plants between studies. Indeed, the fact that several samples allow for a good match between our results and the literature supports such a hypothesis.…”
Section: Optimization Of the Protocolcontrasting
confidence: 72%
“…Although slight, but significant, dissimilarities in the LCB profiles of plant leaves exist between our data and those of others [17,21,33], they are unlikely due to technical issues but rather reflect differences in the physiological status of plants between studies. Indeed, the fact that several samples allow for a good match between our results and the literature supports such a hypothesis.…”
Section: Optimization Of the Protocolcontrasting
confidence: 72%
“…Previously, studies on plant D 8 -sphingolipid desaturase genes such as in B. officinalis and in N. tabacum were focused on only one copy of the gene. Results of these studies showed that the D 8 -sphingolipid desaturase genes were primarily expressed in active developmental tissues (Sperling et al, 2001;García-Maroto et al, 2007). Another study showed that RnD8A and RnD8B were expressed in all the tissues of R. nigrum, but the expression patterns of these two genes were investigated together because they showed very high sequence identities (Song et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Genes encoding plant D 8 -sphingolipid desaturases have been identified from Arabidopsis thaliana, Brassica napus, Helianthus annuus, Borago officinalis, Aquilegia vulgaris, Nicotiana tabacum, Stylosanthes hamata and Ribes nigrum (Sperling et al, 1998(Sperling et al, , 2000(Sperling et al, , 2001Michaelson et al, 2002;García-Maroto et al, 2007;Ryan et al, 2007;Song et al, 2010;Moreno-Pérez et al, 2011). Expression of these cDNA sequences in vivo using S. cerevisiae as a heterologous host resulted in the biosynthesis of both cis-and trans-isomers of plant characteristic 4-hydroxysphing-8-enines, which do not present in wild-type yeast cells (Sperling and Heinz, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…García-Maroto et al (2007) speculated that distinct D8 desaturases might have preferences for the cerebroside or glycosyl inositol phosphorylceramide groups of sphingolipids. The sphingobase phytosphinganine (t18:0) is a candidate substrate for S851 (Sperling et al, 2000).…”
Section: D48mentioning
confidence: 99%